NLRC3, a member of the NLR family of proteins, is a negative regulator of innate immune signaling induced by the DNA sensor STING - Zhang, Lu; Mo, Jinyao; Swanson, Karen V; Wen, Haitao; Petrucelli, Alex; Gregory, Sean M; Zhang, Zhigang; Schneider, Monika; Jiang, Yan; Fitzgerald, Katherine A; Ouyang, Songying; Liu, Zhi-Jie; et al. (Immunity (Cambridge, Mass.), 2014)
Stimulator of interferon genes (STING, also named MITA, MYPS, or ERIS) is an intracellular DNA sensor that induces type I interferon through its interaction with TANK-binding kinase 1 (TBK1). Here we found that the nucleotide-binding, leucine-rich-repeat-containing protein, NLRC3, reduced STING-dependent innate immune activation in response to cytosolic DNA, cyclic di-GMP (c-di-GMP), and DNA viruses. NLRC3 associated with both STING and TBK1 and impeded STING-TBK1 interaction and downstream type I interferon production. By using purified recombinant proteins, we found NLRC3 to interact directly with STING. Furthermore, NLRC3 prevented proper trafficking of STING to perinuclear and punctated region, known to be important for its activation. In animals, herpes simplex virus 1 (HSV-1)-infected Nlrc3(-/-) mice exhibited enhanced innate immunity and reduced morbidity and viral load. This demonstrates the intersection of two key pathways of innate immune regulation, NLR and STING, to fine tune host response to intracellular DNA, DNA virus, and c-di-GMP.